Structural characteristics of Zambias agricultural sector and the role for agricultural policy : insights from SAM based modelling - Mulanda, Stephen Mulanda (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.